Morphological diversity and yellow rust resistance in bread wheat germplasm lines - Khan, MA; Nelwadker, RahulR; Mir, RR; din, Kamalud; Bhat, M Ashraf (Journal of Cereal Research, 2017)
Genetic divesity was studied for ten quantitative traits using D2 statistics in a set of twenty-six wheat germplasm lines studied. The study grouped the genotypes into three clusters. Cluster I comprised of maximum genotypes (16) followed by clustered II (9) and cluster III (1). The mean intra and inter cluster distance (âˆšD2) values revealed that cluster I has the high intra cluster distance value of 16.22 followed by cluster II (16.21). The inter cluster distance D2 value was highest between cluster II and III (41.20) followed by cluster I and cluster II (30.00). This indicates that the genotypes included in cluster II and III have wide genetic diversity and could be used in hybridization programme aimed at direct selection for the traits or improvement of genotypes through exploitation of heterosis. Traits like 1000 grain weight, Plant height and grain yield had more contribution towards genetic divergence, hence these traits are major determinants of genetic diversity in the present set of genotypes. The fourteen germplasm lines have shown higher levels of resistance to prevalent races of yellow rust at adult plant stage during disease screening experiments seperately conducted in two growing seasons of years 2015 and 2016. The yellow rust resistant genotypes identified in the study could further be tested for their effectiveness over space and time. Â Doi.org/ 10.25174/2249- 4065/2017/74853